Bone marrow aspirate clot: A technical complication or a smart approach for musculoskeletal tissue regeneration?. Issue 4 (24th July 2017) - Salamanna, Francesca; Contartese, Deyanira; Nicoli Aldini, Nicolò; Barbanti Brodano, Giovanni; Griffoni, Cristiana; Gasbarrini, Alessandro; Fini, Milena
Abstract : One of the methods employed to improve healing of damaged tissues is the use of cellular based therapies. A number of regenerative medicine based strategies, from in vitro expanded mesenchymal stem cells (MSCs) to "one‐step" procedures using bone marrow (BM) in toto (BM aspirate; BMA) or BM concentrate (BMC), have been developed. Recently, orthopedic researchers focused their attention on the clinical therapeutic potential of BMC and BMA for musculoskeletal regeneration. BMA is reported as an excellent source of cells and growth factors. However, the quality of BM harvest and aspirate is extremely technique‐dependent and, due to the presence of megakaryocytes and platelets, BMA is prone to clot. BMA clot formation is usually considered a complication hampering the procedures on both BMC preparation and MSC expansion. Therefore, different protocols have been developed to avoid and/or degrade clots. However, from a biological point of view there is a strong rationale for the use of BMA clot for tissue engineering strategies. This descriptive systematic literature review summarizes preclinical and clinical studies dealing the use of BMA clot for orthopedic procedures and provided some evidence supporting its use as a cell based therapy for cartilage and bone regeneration. Despite these results, there are still few preclinical and clinical studies that carefully evaluate the safety and efficacy of BMA clot in orthopedic procedures. Thus, implementing biological knowledge and both preclinical and clinical studies could help researchers and clinicians to understand if BMA clots can really be considered a possible therapeutic tool. Abstract : Bone marrow aspirate (BMA) clot formation is usually considered a complication hampering the procedures on both BMC preparation and MSC expansion. From a biological point of view there is a strong rationale for the use of BMA clot for tissue engineering strategies. This descriptive systematic literature review summarizes preclinical and clinical studies dealing the use of BMA clot for orthopedic procedures. There are few preclinical and clinical studies that carefully evaluate the safety and efficacy of BMA clot in orthopedic procedures.